The chemistry of death – Adipocere degradation in modern graveyards. (December 2015) - Fiedler, S.; Berns, A.E.; Schwark, L.; Woelk, A.T.; Graw, M.
Highlights: Exhumation reveals black material on top of adipocere in reducing soil. Black material results from the direct degradation of adipocere. Adipocere can be degraded under poikiloaerobic conditions over short periods. Adipocere degradation occurs by way of aerobic as well as chemical pathways. Abstract: The formation of adipocere slows further decomposition and preserves corpses for decades or even centuries. This resistance to degradation is a serious problem, especially with regard to the reuse of graves after regular resting times. We present results from an exhumation series in modern graveyards where coffins from water-saturated earth graves contained adipocere embedded in black humic material after resting times of about 30 years. Based on the assumption that this humic material resulted from in situ degradation of adipocere, its presence contradicts the commonly held opinion that adipocere decomposition only occurs under aerobic conditions. To test our hypothesis, we collected black humic material, adipocere as well as soil samples above and below coffins from representative graves ( n = 7). A comprehensive chemical analysis of the samples substantiated our in situ degradation theory. Element compositions and fatty acid mass spectra confirmed that the humic black material originated from the corpses. A van Krevelen diagram classified the excavated adipocere material as lipid, whereas the black humic material was closer to the carbohydrate region. Mass fragmentograms of the humic material revealed the presence of large amounts of saturated vs. unsaturated nC16 and nC18 fatty acids, which is typical for adipocere. In addition, the soil samples exhibited a lipid signature deriving primarily from plant waxes and root components (C20 C32 ). Solid-state 13 C NMR spectra of adipocere displayed well-resolved signals of saturated aliphatic chains and a signal that corresponded to carboxylic acid groups. The NMR spectra of the black humic material revealed signals characteristic of long aliphatic chains. The intensities varied in relation to the state of degradation of the sample, as did the signals of oxidized aliphatic chains, acetals and ketals, aromatic structures, esters and amids. The analyses confirmed that the black humic material was indeed derived from adipocere, so the assumption is that the components detected must have developed from aliphatic fatty acids via a number of oxidation and condensation processes. We therefore propose the existence of chemical pathway(s) for the degradation of adipocere under poikiloaerobic conditions. Possible (biogeo)chemical reaction chains include (1) the autoxidation of fatty acids enhanced by haemoglobin, methaemoglobin and haemin, (2) the use of alternative electron acceptors, which leads to the formation of H2 S that then reacts abiotically with iron (from haemoglobin), rendering iron sulphide, and (3) the Maillard reaction. These findings are another step forward in understanding the chemistry of buried corpses.